Evaluasi Program Pembinaan Pusat Pendidikan dan Latihan Pelajar (PPLP) Provinsi Kepulauan Riau - Aditya Vernando Putra; Fitri Kurnianingsih; Chaerey Ranba Sholeh (RISOMA : Jurnal Riset Sosial Humaniora dan Pendidikan, 2024)
The Student Education and Training Center (PPLP) in Riau Islands was formed based on the Ministry of Youth and Sports (KEMENPORA) program in the development of achievement sports coaching centers in the regions. Currently Riau Islands Province has 3 PPLP Sports Branches that are running, namely Pencak Silat, Taekwondo and Archery which are managed by the Riau Islands Provincial Youth and Sports Office. In its implementation there are several shortcomings such as sports facilities, facilities and infrastructure, and the achievements of athletes. The purpose of this study was to obtain a complete picture and evaluate the process of implementing the coaching program for PPLP athletes in Riau Islands Province. This research methodology uses a qualitative descriptive approach with primary and secondary data sources, and data collection methods in the form of documentation, interviews, and observations. The theory used by researchers in evaluation uses Masson & Gibbon's theory in Hayat (2018) which includes indicators: The process has run optimally, seen from the role of the management in implementing the coaching program that has been well coordinated. For formative indicators, it is less than optimal as seen from the fulfillment of athletes' facility needs which are not fully met. For summative indicators, it runs less optimally seen from the results of athletes' achievements that have not been consistent at the national level. The conclusion of this research is that the PPLP program has been running quite well in Riau Islands Province, it's just not optimal seen from additional professionals such as sports specialists, infrastructure and the results of athletes' achievements at the National level. Suggestions for improvement are that the administrators involved in the PPLP program must be able to increase their contribution, especially in terms of meeting the needs of athletes